Dicynodonts and the end Permian event - King, Gilian M (Bernard Price Institute for Palaeontological Research, 1990)
Patterns of diversity changes in several groups of Late Permian South African terrestrial tetrapods are examined. Using data contained in Kitching (1977), histograms are presented which illustrate changes in a) total number of tetrapod genera per biostratigraphic zone; b) total number of therapsid genera per zone; c) total number of herbivore genera per zone; and d) total number of carnivore genera per zone. Herbivorous and carnivorous genera are categorized as comprising small, medium or large individuals and histograms which document changes in number of genera in each of these six categories per zone are presented. Potential sources of error inherent in the data are outlined. Broad changes in generic diversity are noted and possible explanations for these changes are presented. It is concluded that the present data do not provide overwhelming evidence for a rapid and catastrophic drop in terrestrial tetrapod diversity at the very end of the Permian, but do illustrate a gradual and continuing decrease from the middle of the Late Permian into the middle of the Triassic.
Keywords: diversity; extinction; Permo-Triassic